The relationship between self-efficacy in blood sugar management and self-management in type 2 diabetes patients at Subang General Hospital - Alifia, Dianita; Minanton, Minanton; Nirwana, Bayu (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Type 2 diabetes mellitus requires effective self-management to prevent complications and maintain a healthy quality of life. Self-efficacy, or a patient’s belief in their ability to manage their condition, is recognized as a key factor influencing diabetes self-management. However, the strength and nature of this relationship remain understudied in the local context of patients receiving care at Subang General Hospital. Purpose: This study aims to investigate the relationship between self-efficacy in blood sugar management and self-management in type 2 diabetes patients at Subang General Hospital. Methods: A quantitative correlational study with a cross-sectional design was conducted. Consecutive sampling was used to recruit 40 respondents. Data were collected using two standardized tools: the Diabetes Management Self-Efficacy Scale (DMSES) and the Diabetes Self-Management Questionnaire (DSMQ). The relationship between self-efficacy and self-management was analyzed using the Spearman-Rho statistical test. Results: Among the respondents, 80% (n=32) demonstrated high levels of self-efficacy, while 67.5% (n=27) exhibited good self-management practices. The statistical analysis revealed a significant positive correlation between self-efficacy and self-management (p=0.003). Conclusion: The findings indicate a significant relationship between self-efficacy and self-management in patients with type 2 diabetes mellitus. These results underscore the importance of enhancing self-efficacy as part of diabetes education and management strategies to improve patient outcomes. Future research should explore interventions that specifically target improving self-efficacy to optimize self-management behaviors.